Sustainable decolorization of methyl blue and malachite green from an aqueous environment using magnetic biochar prepared from the fruit seeds of Mespilus germanica L. - Bayram, Okan; Ozkan, Ugur; Kardes, Serkan; Moral, Emel; Gode, Fethiye; Pehlivan, Erol (Taylor & Francis Ltd, 2025)
The purpose of this study was to assess the properties of nano-iron loaded biosorbent produced from Mespilus germanica L. fruits seed biochar (MGLfsB) powder, as well as the adsorption/desorption properties of two commonly used dyes; Methyl Blue (MB), and malachite green (MG). Mespilus germanica L. fruits seed biochar (nM-MGLfsB) was produced and used as a biosorbent to remove MB and MG from the solution. SEM and FT-IR analysis were used to characterize the prepared nM-MGLfsB. Temperature (303-333 K), pH (2.0-9.0), initial dye concentration (5-200 mg/L), nM-MGLfsB mass (0.1-0.9 g) and contact time (15-240 min) were all tested in batches to see how they influenced adsorption. The Freundlich, Langmuir, Scatchard, and Temkin models were used to analyze the equilibrium adsorption data. The Langmuir isotherm properly represented the adsorption data, and the saturated maximum removal of nM-MGLfsB determined using this model was 13.09 mg/g for MB and 28.33 mg/g for MG. For MB, nM-MGLfsB had a Delta S degrees value of 63.974 and a Delta H degrees value of 8.05; for MG, the values were 49.660 and 3.490, respectively. The results indicate that the nM-MGLfsB can effectively overcome the limitations of using nano-iron alone and achieve highly efficient dyes removal.
Keywords: Mespilus germanica L; methyl blue; malachite green; artificial neural networks